Assessment of yield gaps and income augmentation through participatory cluster front-line demonstrations on Indian mustard (Brassica juncea) in Rajasthan (Journal of Oilseed Brassica, 2026)
Present study assessed the yield gaps and income augmentation of 15670 CFLDs on Indian mustard (Brassica juncea L.) for the period 2015 to 2020 in 5417.45 hectares (ha) through the Krishi Vigyan Kendras (KVKs) in Rajasthan state. The researcher found the yield of CFLDs higher (18.59q/ha) than farmers’ practices (14.70q/ha). The study depicted, the technology gap of 7.54q/ha, the extension gap of 3.89q/ha, and a technology index of 28.26%. The CFLDs realized an additional yield of 3.89q/ha. Subsequently, Rs.15337.00/ha is supplemented, making a total of Rs.9.63 crores. The yields of CFLDs surpassed the state yield by 7.02q/ha and the national yield by 7.53q/ha. The identified technology gaps are attributed to dissimilarity in soil fertility status, weather conditions, and climate vulnerability. However, the adoption of integrated crop management practices could reduce the extension gaps in Indian mustard. Therefore, the professionals of KVKs should adopt location-specific extension methodologies for approaching partner farmer’s for enhancing the yield and production of Indian mustard in Rajasthan. Moreover, the lower value of the technology index indicates greater technology feasibility in the particular district.